Analysis of the Influence of Price, Product Quality, and Brand Image on Consumer Purchase Decisions at Matahari Departement Store in Palopo City - Nurjannah, Nurjannah; Mahmut, Cici; Wanti, Wanti; Nadia, Nadia; Tahir, Muhammad Arul (Universitas Syiah Kuala, 2025)
This study aims to analyze the influence of price, product quality, and brand image on consumer purchasing decisions at Matahari Department Store in Palopo City. As competition intensifies in the modern retail sector, especially in fashion, understanding the factors that drive consumer choices becomes increasingly vital. The research employed a quantitative method using multiple linear regression analysis to process data collected through observation, interviews, and questionnaires from 50 respondents. The findings reveal that price and brand image have a significant influence on consumer purchase decisions, while product quality does not have a statistically significant effect. This suggests that in this retail context, consumers place greater emphasis on perceived value and brand reputation rather than product quality, which is assumed to meet standard expectations. These results underscore the need for retail businesses to focus on competitive pricing and brand development strategies in order to enhance consumer engagement and purchasing behavior. The study provides valuable insights for marketing practitioners seeking to align business strategies with evolving consumer preferences in mid-sized urban markets.